2021
DOI: 10.1021/acs.jpcb.1c01982
|View full text |Cite
|
Sign up to set email alerts
|

Elongation of Triplet Lifetime Caused by Intramolecular Energy Hopping in Diphenylanthracene Dyads Oriented to Undergo Efficient Triplet–Triplet Annihilation Upconversion

Abstract: Triplet-triplet annihilation (TTA)-assisted photon upconversion (TTA-UC) in three dyads (DPA-Cn-DPA), comprised of two diphenylanthracene (DPA) moieties connected by nonconjugated C1, C2, and C3 linkages (Cn), has been investigated. The performance of these dyads as energy acceptors in the presence of the energy donor platinum octaethylporphyrin are characterized by longer triplet lifetimes (tT) and different TTA rate constants than those of the parent DPA. The larger tT of the linked systems, caused by "Intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…This molecular conformation corresponds to a distance between the two phenyl groups around 8.3 Å and a distance between the C9 and C9′ position of the DPA groups is 9.9 and 10.2 Å for PAPF and PAPE ( Figure S2, Supporting Information ) , respectively. As reported by Ikeda et al, [16a] the molecules exhibiting different emission behaviors from the DPA chromophore such as reducing threshold intensity and increasing TTA rate with the distance of two DPA groups ranging from 8.3 to 12.3 Å. Note that TTA requiring the Dexter type energy transfer, which is efficient when the distance between the two triplet species 3 DPA* is smaller than 10 Å.…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…This molecular conformation corresponds to a distance between the two phenyl groups around 8.3 Å and a distance between the C9 and C9′ position of the DPA groups is 9.9 and 10.2 Å for PAPF and PAPE ( Figure S2, Supporting Information ) , respectively. As reported by Ikeda et al, [16a] the molecules exhibiting different emission behaviors from the DPA chromophore such as reducing threshold intensity and increasing TTA rate with the distance of two DPA groups ranging from 8.3 to 12.3 Å. Note that TTA requiring the Dexter type energy transfer, which is efficient when the distance between the two triplet species 3 DPA* is smaller than 10 Å.…”
Section: Resultsmentioning
confidence: 67%
“…[ 15 ] Furthermore, Ikeda et al clearly showed that the critical factor ( I th) for judging the efficiency of TTA‐UC was lower for the σ‐spacer linked DPA dimer with a sufficiently close interchromophore distance as compared to that of the DPA monomer and concluded that intra‐TTA was operative. [ 16 ] Fundamentally, the distance between annihilators is not the only factor that affects intra‐TTA behavior. The relative configuration between chromophores is of great importance as well.…”
Section: Introductionmentioning
confidence: 99%
“…A triplet energy donor (photosensitizer) and energy acceptor (triplet annihilator/emitter) are key components in typical TTA-UC systems. , Owing to highly efficient intersystem crossing by strong spin-orbit coupling (SOC), photosensitizers typically employ transition metals (Pt, Pd, Ru, and Ir) or heavy atoms (I and Br) to populate triplet excitons. In recent years, some pure organic photosensitizers have also been developed for TTA-UC including thermally activated delayed fluorescence materials, fullerene (C 60 and C 70 ) derivatives, and spin-orbit charge transfer intersystem crossing molecules. Nonetheless, the absorption bands of most photosensitizers are mainly distributed in the visible region, and TTA-UC pairs that are able to convert light from deep-red (>650 nm)/near-infrared (NIR) to visible region remain scarce (Table S1). …”
Section: Introductionmentioning
confidence: 99%
“…The well-studied system of palladium­(II) octaethylporphine (PdOEP) and 9,10-diphenylanthracene (DPA) was selected from a library of a few dozen TTA pairs as it has been shown to upconvert even in nonideal conditions such as in polymer matrices. , Palladium stabilizes the triplet state of the porphyrin molecule and increases its lifetime to 50–250 μs, which enables TTA at low light intensities. Typical DPA triplet lifetimes are long, at ∼0.1–1 ms, leading to a reasonably high probability of TTA occurring. , The photoinitiator, Irgacure 2100 (I2100), was selected because its absorbance overlaps with the emission of DPA and because its liquid nature facilitates homogeneous mixing. Ethoxylated trimethylopropane triacrylate (ETPTA) was selected as the monomer to reach gelation quickly during 3D printing.…”
mentioning
confidence: 99%